StudiCare mindfulness—study protocol of a randomized controlled trial evaluating an internet- and mobile-based intervention for college students with no and “on demand” guidance - Küchler, Ann-Marie (Trials, 2020)
BACKGROUND: College is an exciting but also challenging time with an increased risk for mental health issues. Only a minority of the college students concerned get professional help, a problem that might be improvable by internet- and mobile-based interventions (IMIs). However, adherence of IMIs is a concern. While guidance might be a solution, it is resource-intensive, derailing potential implementation on population level. The first aim of this trial is to evaluate the efficacy of the IMI StudiCare Mindfulness (StudiCare-M) for college students with “on demand” and no guidance. The second aim is to examine potential moderators and mediators, contributing to the questions of “how” and “for whom” such interventions work. METHODS: In this three-armed randomized controlled trial, both an unguided and “guidance on demand” (GoD) condition of StudiCare-M are compared to a waitlist control group. StudiCare-M is based on principles of acceptance and commitment therapy and stress management and consists of 7 modules plus two booster sessions. Participants in the GoD condition may ask their e-coach for support whenever needed. A total of 387 college students with moderate to low mindfulness are recruited at 15+ cooperating universities in Germany, Austria, and Switzerland via circular emails. Assessments take place before as well as 1, 2, and 6 months after randomization. The primary outcome is mindfulness. Secondary outcomes include stress, depression, anxiety, interoception, presenteeism, wellbeing, intervention satisfaction, adherence, and potential side effects. Among examined moderators and mediators are sociodemographic variables, pre-treatment symptomatology, treatment expectancy, self-efficacy, cognitive fusion, emotion regulation, and alexithymia. All data will be analyzed according to intention-to-treat (ITT) principles. DISCUSSION: Providing effective interventions to help college students become more resilient can make a valuable contribution to the health and functionality of future society. If effective under the condition of minimal or no guidance, StudiCare-M offers a low-threshold potentially resource-efficient possibility to enhance college student mental health on a population level. Moderation- and mediation analyses will deliver further insights for optimization of target groups and intervention content. TRIAL REGISTRATION: WHO International Clinical Trials Registry Platform via the German Clinical Studies Trial Register DRKS00014774. Registered on 18 May 2018.